A real-world study comparing pre-post billed annualized bleed rates and total cost of care among non-inhibitor patients with hemophilia A switching from FVIII prophylaxis to emicizumab. (3rd October 2022) - Batt, Katharine; Schultz, Bob G.; Caicedo, Jorge; Hollenbeak, Christopher S.; Agrawal, Neha; Chatterjee, Sagnik; Bullano, Michael
Abstract: Objective: Factor VIII (FVIII) replacement and emicizumab have demonstrated efficacy for prevention of bleeds among patients with hemophilia A (PwHA) compared to on-demand (OD) use. Evidence investigating clinical outcomes and healthcare costs of non-inhibitor PwHA switching from prophylaxis with FVIII concentrates to emicizumab has not been well-established within large real-world datasets. This study aimed to investigate billed annualized bleed rates (ABRb ) and total cost of care (TCC) among non-inhibitor PwHA switching from FVIII-prophylaxis to emicizumab-prophylaxis. Methods: This retrospective, observational study was conducted using IQVIA PharMetrics Plus, a US administrative claims database. The date of first claim for emicizumab was defined as the index date. OD patients and inhibitor patients were excluded. Bleeds were identified using a list of 535 diagnosis codes. Bayesian models were developed to estimate the probability ABRb worsens and TCC increases after switching to emicizumab. Wilcoxon rank-sum tests were used to test statistical significance of changes in ABRb and TCC after switch. Results: Among the 121 identified patients, the difference in mean ABRb between FVIII-prophylaxis (0.68 [SD = 1.28]) and emicizumab (0.55 [SD = 1.48]) was insignificant ( p  = .142). The mean annual TCC significantly increased for patients switching from FVIII-prophylaxis ($518, 151 [SD = $289, 934]) to emicizumab ($652, 679 [SD = $340, 126]; p  < .0001). The Bayesian models estimated a 21.0% probability of the ABRb worsening and a 99.9% probability of increasing TCC after switch. Conclusions: This study found that in male non-inhibitor PwHA, switching from FVIII prophylaxis to emicizumab incurs substantial cost increase with no significant benefit in ABRb . This evidence may help guide providers, payers, and patients in shared decision-making conversations around best treatment options.